Association of lower liver function with cognitive impairment in the Shenzhen ageing-related disorder cohort in China - Wu, Kaiyu; Xu, Chunyan; Qiu, Guozhen; Guo, Qiwen; Chen, Chunchun; Liu, Wei; Liu, Jianjun; Liu, Kangding; Zhu, Feiqi (Frontiers in Aging Neuroscience, 2022)
Background Accumulating evidence suggests that alterations in liver function may play an important role in the pathogenesis of Alzheimer’s disease (AD). However, it remains unclear whether there is any relationship between lower liver function and cognitive impairment among the elderly. Methods From 2017 to 2018, we recruited 7,201 older people (over 60 years old) from 51 community health centers in the Luohu District of Shenzhen City. According to the Mini-Mental State Examination (MMSE) score and education level, participants were divided into a cognitive impairment group (n = 372) and a normal cognitive function group (n = 6,829). Nonparametric test, chi-square tests, and binary logistic regression were used to analyze the data. Results Cognitive impairment group exhibits older age, more female sex, lower education level, and lower levels of albumin and triglyceride. Additionally, the aspartate aminotransferase (AST) to alanine aminotransferase (ALT) ratio was mainly distributed in the range of 1.17 to 1.3 in the cognitive impairment group, and 0.85 to 1.00 in the normal cognitive function group (χ2 = 10.02, p = 0.04). Binary logistic regression showed that cognitive impairment was significantly associated with age (OR = 0.934, 95%CI: 0.886–0.985, p = 0.017), female sex (OR = 2.255, 95%CI: 1.761–2.888, p < 0.001), lower education level (less than senior high school) (OR = 11.509, 95%CI: 9.064–14.613, p < 0.001), and lower albumin (OR = 1.023, 95%CI: 1.004–1.043, p = 0.011). Conclusion Except for age, female sex, and lower education level, lower level of albumin and elevated AST to ALT ratio correlate with cognitive impairment. Whether lower liver function plays a role in AD needs to be further studied.